Tragedy, philosophy, and political education in Plato's "Laws" - Balot, Ryan K. (Oxford University Press, Incorporated, 2024)
Cover -- Tragedy, Philosophy, and Political Education in Plato's Laws -- Copyright -- Dedication -- Contents -- Preface and Acknowledgments -- 1. Introduction: Interpreting Plato's Laws -- The Athenian's Ambitions and Ambivalence -- Scholarly Approaches and Methods -- Who Is the Athenian Stranger? -- The Argument -- 2. The Character of Kleinias -- The Education of Kleinias as a Framework for the Dialogue -- Kleinias at First Sight: Cynical, Fearful, Acquisitive, Thumoeidetic -- Down to the Foundations: Kleinias' Materialism -- The Athenian's Teleological Reply: Souls, Goats, Symposia, and Cities -- Communities of Practice: Goats, Symposia, and Cities -- Kleinias' Tyrannical Ambitions -- Consonance Achieved through the Advent of a "God" -- 3. The Politics and Psychology of Human History -- The Archaeology of Kleinias: Early Human History -- The Early History of Lacedaimon and the Dorians -- The Regime's Goal: A Retrospective Account -- Ignorance and Wisdom: A New Interpretation -- Fortifying the Law against Tyrants -- The Self-​Destructiveness of Persian Tyranny -- Reinterpreting Democracy in Archaic Athens -- 4. A New Beginning: Founding Magnesia -- The "Existential" Framework -- The True Legislator and the Young Tyrant -- Religion and the New Regime -- Rule of Law, Rule of Nous -- Thrasymachus' Challenge and the Seven Titles to Rule -- Conclusion: Direct and Indirect Rule -- 5. Persuasive Preambles -- Preambles and the Two Doctors at a Glance -- Persuasion versus Force: Revisiting the Case of the Young Tyrant -- The Athenian's Purposes: "Tameness" and "Savagery" -- Hesiod and the Athenian on the Benefits of Virtue -- The Lawgiver and the Poets -- "Caring" Legislation: Persuasion toward Eudaimonism -- Free Doctor and Slave Doctor: Persuasion, Trust, and Nature -- Reason and Emotion in the Preambles.